PENDIDIKAN AKHLAKUL KARIMAH BERBASIS KARAKTER MELALUI PENDEKATAN TEORI EKOLOGI BRONFENBRENNER - Emi Fahrudi (PREMIERE : Journal of Islamic Elementary Education, 2021)
Moral education is a fundamental education that must be fulfilled in all generations of the nation because it determines the quality of a nation in the future, at this time along with the development of the era in the digital information era, the phenomenon of dishonorable actions such as the courage of children to parents, lack of courtesy, courtesy, brawls, theft, and mischief of other children. One of the triggering factors for this to happen is the low quality of morals that become a character, the effect of moral and character education is carried out partially, not through a holistic approach. The theory of developmental ecology is one of the theories that describes character-based education, the theory adheres to three systems, namely; microsystems, ecosystems and macrosystems